Comparison of Elecsys Anti‐HCV II Assay With Other HCV Screening Assays. Issue 5 (14th December 2015) - Li, Dongdong; Zhu, Siyuan; Wang, Tingting; An, Jingna; Wang, Lanlan; Tao, Chuanmin
Abstract : Objective: Early detection of hepatitis C virus (HCV) is an important step in preventing progression to cirrhosis and hepatocellular carcinoma. Serologic assays for anti‐HCV antibody are valuable first‐line tests in the screening and diagnosis of HCV infection. This study's aim was to evaluate the sensitivity and specificity of Elecsys Anti‐HCV II assay for HCV screening. Design and Methods: A total of 1, 044 routine sera, 20 known HCV‐positive samples, plus 54 preselected weakly positive samples were tested for anti‐HCV with Elecsys Anti‐HCV II assay, Elecsys Anti‐HCV assays, InTec HCV enzymoimmunoassay (EIA), and Livzon Anti‐HCV EIA. Interference test was assessed with additional 423 specimens without clinical evidence of HCV infection: preselected HCV weak reactive samples; dialysis samples; anti‐HBc (antibody to HBV core antigen) (+), anti‐ Treponema pallidum (+), and anti‐HIV (+) sera; and samples form autoimmune/alcoholic hepatitis or systemic Lupus erythematosus (SLE). Discrepant results were evaluated with recombinant immunoblot assay. The seroconversion panels were evaluated to assess how early each assay could detect HCV infection. Results: The specificity (99.81%) of the Elecsys Anti‐HCV II assay was less than that with the two EIA comparison methods. However, false‐negative results were easily seen in the EIA assays. When serial bleeds of HCV panels were compared with the above‐mentioned methods, the assay detected acute HCV infection only 3.5 days after a positive HCV‐RNA nucleic acid test and earlier than the comparator assays. Conclusion: Sensitivities and specificities of the anti‐HCV assays were sufficiently high for use in this study. The Elecsys Anti‐HCV II assay is suitable for screening and reliable early detection of HCV infection.